Correlation of quality of life with executive function of brain in blind veterans - V. Nejati; R. Amini; A. Zabihzadeh (Afarand Scholarly Publishing Institute, 2012)
Background and Goal: Quality of life is a universal but abstract, mental and global concept that should be reduced to concrete, palpable and local part. The purpose of present study is evaluation of correlation of quality of life dimension with executive function of brain in blind veterans. Method: in this cross sectional study 93 blind veterans were participated. SF36 and De executive test are used for evaluation. Pearson correlation test is used for data analysis. Result: Physical and mental dimension of quality of life is correlated with all aspect of executive function without hyperactivity. (P value <0.01 for physical component and <0.05 for mental component) Conclusion: Executive functions are proper predictor of quality of life in blind veterans. This project with support of additional interventional study proposes executive function rehabilitation for promotion of quality of life in blind veterans.